Comparison of Short-Term Clinical Outcome of Non-ST Elevation versus ST Elevation Myocardial Infarction - Hakimeh Sadeghian; Mehrdad Sheikhvatan; Mehran Mahmoodian; Mahmood Sheikhfathollahi; Elham Hakki; Afsaneh Sadeghian; Behnaz Behnam; Ali Mohammad Haji Zeinali; Vahid Semnani (Journal of Tehran University Heart Center, 2009)
Background: Studies on the prognosis of ST elevation myocardial infarction (STEMI) versus non-ST elevation myocardial infarction (non-STEMI) have shown different results. The present study was designed to compare the early outcome and left ventricular systolic function of patients with ST and non-ST elevation myocardial infarction.